Copper‐Catalyzed Enantioselective Cyano(Fluoro)Alkylation of Alkenes. Issue 11 (18th May 2020) - Israr, Muhammad; Xiong, Haigen; Li, Yajun; Bao, Hongli
Abstract: A copper‐catalyzed asymmetric cyano(fluoro)alkylation reaction of alkenes is reported. A range of chiral fluoroalkyl cyanides were obtained in high yields and excellent enantiomeric excess from readily available chemicals. The method uses fluoroalkyl iodides as the fluoroalkyl source and employs mild conditions. The peroxide LPO plays a significant role in promotion of this radical asymmetric reaction. Abstract :